Simulação hidrossedimentológica da bacia do rio Vacacaí Mirim - Batistel, Leonardo (2018)
Modeling has been shown to be an important tool to aid in the planning and management of water resources in river basins. Thus, the hydrosedimentological modeling of the catchment area of the Vacacaí Mirim river seeks to simulate the sedimentological behavior through the estimation of sediment production and transport. The work used the HEC-HMS hydrological model to perform the hydrosedimentological simulation of the basin. The input data of the model were obtained from BDGHIDROS, ANA, INMET and CPTEC. A liquid discharge key curve with superior extrapolation and a solid discharge key curve for the period considered (2007–2016) was established. Model input parameters such as Curve Number (CN) and MUSLE factors were obtained from the analysis of physiographic characteristics of the basin by geoprocessing techniques. The calibration of the model considered the period from 2008 to 2011 and returned quite satisfactory values for the coefficients of performance of the model. The Nash-Sutcliffe (NS) efficiency coefficient presented a value of 0,791, the Percent BIAS coefficient (PBIAS) presented value of -0,003% and the RSR coefficient presented a value of 0,457. For the validation of the model, the period from 2012 to 2016 was used. The validation of the model presented satisfactory performance values. The NS coefficient presented a value of 0,560, the PBIAS coefficient presented a value of -1,332% and the RSR coefficient showed a value of 0,663, which indicates adequacy of the model. The negative sign values for the PBIAS indicate overestimation of the model in relation to the observed data. The hydrosedimentological simulations were carried out for the same periods considered in the calibration and validation of the model and were evaluated using the total solid discharges calculated and observed and for all methods of calculation of potential sediment transport. The first simulated period (2008–2011) presented unsatisfactory values for the model performance coefficients for all sediment transport potential calculation methods. For the second simulated period (2012-2016) the Engelung-Hansen method was the only one that presented satisfactory values for the coefficients of performance of the model. The value of the NS coefficient was 0,531, the PBIAS coefficient was 43,686% and the RSR coefficient was 0,685. Another method used to evaluate sediment yield and transport was the sediment delivery ratio (SDR), which presented values of 20,56% for the calculated total solid discharge and 64,13% for that observed for the first simulated period, for the Engelund-Hansen method. For the second simulated period, the values were 26,52% for the calculated total solid discharge and 47,09% for the total solid discharge observed, also for the Engelund-Hansen method. The SDR values were calculated considering the calculated volumes of sediment produced by MUSLE. The SDR values for the total solid discharges of both simulated periods presented values compatible with values obtained in the literature.